2013
DOI: 10.4028/www.scientific.net/amr.829.874
|View full text |Cite
|
Sign up to set email alerts
|

Application of Nano Silica in Concrete for Enhanced Resistance against Sulfate Attack

Abstract: Durability of concrete structure is a critical issue especially in severe environment when the concrete structure is exposed to sulfate attack, such as shorelines. nanoSilica is high pozzolanic material which is used recently in concrete to improve its mechanical properties. However, the durability of concrete against sulfate attack containing nanoSilica (NS) has not been investigated completely. In this study, the effects of NS has been studied on compressive strength, sulfate attack and morphology characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 8 publications
0
15
0
4
Order By: Relevance
“…As a result of the NS grains' capacity to act as an inner filler inside the cementitious mix, the NS may be utilized to lower the permeability of the concrete by refining the pore structure. Arel and Thomas [165] studied the efficacy of NS and micro-silica as a partial substitute for cement in the presence of sulphate assaults. Their mortar mixes had a w/c of 0.5 and were subjected to a 7% sodium sulphate solution for 23 weeks.…”
Section: Sulphate Resistancementioning
confidence: 99%
“…As a result of the NS grains' capacity to act as an inner filler inside the cementitious mix, the NS may be utilized to lower the permeability of the concrete by refining the pore structure. Arel and Thomas [165] studied the efficacy of NS and micro-silica as a partial substitute for cement in the presence of sulphate assaults. Their mortar mixes had a w/c of 0.5 and were subjected to a 7% sodium sulphate solution for 23 weeks.…”
Section: Sulphate Resistancementioning
confidence: 99%
“…Another study on self-compacting concrete confirmed this trend, where the water absorp-tion, capillary absorption and chloride ions penetration are reduced with the addition of nano-SiO 2 (Jalal et al 2012). The resistance against sulfate attack increases and the water permeability decreases, with the addition of nano-SiO 2 (Du et al 2014;Ji 2005;Moslemi et al 2014). The nano-Al 2 O 3 also contribute to a better durability performance, since a study conducted by Kiachehr and Niloofar (2013) concluded that concrete containing nano-Al 2 O 3 improved the freeze-thaw resistance.…”
Section: Introductionmentioning
confidence: 88%
“…In the equilibration stage, the NVT ensemble was used for 700 ps to relax all the SO 2 configurations, whereas in the production stages, the simulations were performed in the NVE ensemble for 3000 ps, obtaining the MSD plots. It is worthy of mentioning that, for relaxation purposes, a less accurate NVT method is sufficient; however, to achieve more profound insight into the trajectories, the NVE ensemble gives more reliable and accurate results. ,, The equations of motion were integrated using the Verlet leapfrog algorithm with 1.0 fs time step. To investigate the loading effect, the simulations were performed with 4, 8, 16, and 32 molecules of SO 2 in each UC.…”
Section: Simulation Details and Methodsmentioning
confidence: 99%